16S rRNA Barcoding technique for species identification of processed sea cucumbers from selected Malaysian markets - Kamarudin, Kamarul Rahim; Mohamed Rehan, Maryam; Mohd Noor, Hanina; Ramly, Nur Zazarina; Mohamed Rehan, ‘Aisyah (Universiti Pendidikan Sultan Idris, 2016)
In food industry, wide-ranging processing of sea cucumbers (Phylum Echinodermata: Class Holothuroidea) including gutting, boiling, roasting, and subsequent preservation procedures are frequently needed prior to marketing. These processes cause body deformation of the sea cucumbers, thus leading to difficulties in species identification and confirmation of the processed sea cucumbers or beche-de-mer. Furthermore, beche-de-mer products in Malaysian markets are often unlabelled or mislabelled. Economic fraud, health hazards, and illegal trade of protected species are the potential major consequences of the issues. Therefore, a reliable, reproducible, and rapid technique for species identification is required. For that reason, this study was conducted to determine species identity of 25 beche-de-mer specimens that were not tagged with species details from four selected Malaysian markets. Five reference samples were also included in the analyses consisting of fresh samples that were morphologically identified as Stichopus horrens and Holothuria (Mertensiothuria) leucospilota from Pangkor Island, Perak, Malaysia. Phylogenetic analyses of 30 partial sequences of non-protein-coding 16S mitochondrial ribosomal RNA (rRNA) gene using five main methods i.e. Neighbour-Joining (NJ), Maximum Likelihood (ML), Minimum Evolution (ME), Unweighted Pair Group Method with Arithmetic Mean (UPGMA), and Maximum Parsimony (MP) showed the presence of two main clusters of the beche-demer specimens: Stichopodidae (gamat family) and Holothuriidae (timun laut family). The beche-de-mer specimens of S. horrens, Stichopus herrmanni, and Thelenota anax were the three gamat species that clustered under the family Stichopodidae. Meanwhile, the beche-de-mer specimens of H. leucospilota, Holothuria (Halodeima) edulis, Holothuria (Metriatyla) scabra, and H. scabra var. versicolor were the four timun laut species that clustered under the family Holothuriidae. In fact, the outcomes of this study suggested the potential of 16S mitochondrial rRNA gene sequencing technique to be used by the enforcement agencies in monitoring and overcoming the issues of species substitution and product mislabeling of beche-de-mer products in Malaysian markets.